MODEL ANALISIS PENGAWASAN BPD DAMPAKNYA PADA TRANSPARANSI KEUANGAN DESA MELALUI APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DI KABUPATEN TANGERANG DENGAN KINERJA PERANGKAT DESA SEBAGAI MODERASI - Doddy Mulyono (iLearning Journal Center, 2020)
This study aims to analyze the influence of BPD supervision that has an impact on transparency in village financial management with performance variables as moderation. This research model is very important to provide input in good village financial management. If the BPD supervision process goes well, the performance of village officials can be optimal so that village development will be successful. This study took 152 samples of village officials in Tangerang district, this study used AMOS structural equation modeling (SEM) analysis. The results of this study indicate that BPD supervision has a positive and significant impact on village financial transparency, but the performance variable is not able to moderate BPD supervision over village financial transparency. This research model is very unique because it can be an evaluation for stakeholders, especially the village government in increasing the supervisory role of the BPD to improve the performance of village officials, thus, village financial transparency will be well realized for the welfare of village communities through the development.